Risk Management Strategies in the Tourism Industry: Developing an ANP Model for Risk Reduction and Resilience Enhancement Amid Crises - ., Marbawi; Dharma, Yulius; Faliza, Nur; Fakhrial, Harris; Malinda , Rina (Journal of Ecohumanism, 2024)
This study investigates risk management strategies in the tourism industry by developing an Analytic Network Process (ANP) model that aims to increase resilience and reduce risks during crises. The tourism sector is inherently vulnerable to a variety of uncertainties, including natural disasters, economic fluctuations, and global health emergencies. Through a comprehensive analysis of key factors such as destination characteristics, stakeholder capacity, regulation, and market dynamics, the study identifies three key strategies: Integrated Public-Private Collaboration Model, Adaptive and Resilient-Based Model, and Smart Technology-Based Model. The results show that the Adaptive and Resilient-Based Model is a top priority for effective risk mitigation, emphasizing the importance of flexibility and adaptability. The results showed that the Adaptive and Resilient-Based Model is a top priority for effective risk mitigation, emphasizing the importance of flexibility and adaptability. Key elements supporting this model include robust infrastructure, advanced technology, skilled human resources, and strong collaboration between stakeholders. The findings provide practical guidance for policymakers and industry stakeholders, highlighting the importance of innovative and sustainable approaches to strengthen the tourism industry’s resilience to dynamic risks and crises.